2020
DOI: 10.1021/acsabm.0c00772
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale Evidence Unravels Microalgae Flocculation Mechanism Induced by Chitosan

Abstract: In light of climate change, there is a growing interest for sustainable energy. Microalgae are a promising resource for biofuel production, although their industrial use is limited by the lack of effective harvesting techniques. Flocculation consists in the aggregation and adhesion of cells into flocs that can be more easily removed from water than individual cells. Although it is an efficient harvesting technique, contamination is a major issue as chemical flocculants are often used. An alternative is to use … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 30 publications
(51 citation statements)
references
References 54 publications
6
37
0
Order By: Relevance
“…This is a major advancement as it will open the possibility to engineer bubbles and this way exploit their full potential in various application fields. For instance, our team is at the moment using this strategy to engineer a new flotation process to harvest microalgae cells, by functionalizing the bubble surface with amphiphilic chitosan, a molecule that we have already shown to promote microalgae aggregation [32]. In future projects, this strategy could also be used to specifically separate cell populations from each other; for example to separate bacterial cells from human blood cells in the case of sepsis, but many other applications can now be envisioned.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is a major advancement as it will open the possibility to engineer bubbles and this way exploit their full potential in various application fields. For instance, our team is at the moment using this strategy to engineer a new flotation process to harvest microalgae cells, by functionalizing the bubble surface with amphiphilic chitosan, a molecule that we have already shown to promote microalgae aggregation [32]. In future projects, this strategy could also be used to specifically separate cell populations from each other; for example to separate bacterial cells from human blood cells in the case of sepsis, but many other applications can now be envisioned.…”
Section: Discussionmentioning
confidence: 99%
“…An aperture at the end of the cantilever allows liquids to be dispensed locally. In this configuration, FluidFM technology has been used in various types of studies in material science, for example to functionalize surfaces with polymer layers [30], or in life sciences for example to perform single-cell force spectroscopy experiments [31,32]. In this study, we use FluidFM in an original manner, and develop a method to produce stable microsized bubbles at the aperture of FluidFM cantilevers.…”
Section: Probing the Interactions Between Air Bubbles And (Bio)interfaces At The Nanoscale Using Fluidfm Technology Introductionmentioning
confidence: 99%
“…The maximal downward bending of the cantilever is directly proportional to the interaction force between the two molecules. The technique can also be used to explore intercellular interaction forces, by attaching mammalian, fungal or bacterial cells onto the lever and/or the substrate [ 88 ]. Since bacteria adhesive properties play an important role in biofilm formation, several teams have used AFM to explore this parameter on various surfaces [ 89 , 90 , 91 ].…”
Section: The Atomic Force Microscope (Afm) and The Cantilever As Amentioning
confidence: 99%
“…A similar study was also reported by Demir et al, (2020) on the flocculation of microalgae in chitosan, where effective flocculation was observed at pH < 6.5 based on the electrostatic interactions between chitosan and the negative cell surface of microalgae. On the other hand, a different mechanism was found upon increasing the pH with metal hydroxides whereby precipitation of chitosan occurred instead of flocculation [46].…”
Section: Coagulation-flocculation Mechanism Of Chitosan and Al-based Coagulantmentioning
confidence: 99%